Experimental investigation on performance of cantilever CFRP-wrapped circular RC columns under lateral low-velocity impact. (15th June 2020) - Xu, J.J.; Demartino, C.; Shan, B.; Heo, Y.A.; Xiao, Y.
Abstract: The main goal of this study is to investigate the effectiveness of seismic retrofit using CFRP wrapping in reducing the damage and preventing the failure of RC bridge piers under vehicular impacts. This paper reports the results of an experimental investigation on the performance of cantilever CFRP-wrapped circular RC columns under lateral low-velocity impact. To this aim, a total of nine 1/3-scale cantilever columns without axial load, comprising three types of shear-deficient RC columns with different reinforcement layout, were tested in a horizontal collision facility at two different impact velocities. The columns were tested in plain configuration (0 plies) and two wrapped configurations with 2 and 4 plies of CFRP. Generally, for plain columns, brittle shear-type damage was observed. Larger damage was obtained by increasing the impact velocity and decreasing the amount of transverse reinforcements while the variation of the amount of longitudinal steel bars has a negligible effect. The experimental results demonstrate that seismic retrofit using CFRP can provide an effective solution to convert the failure mechanism under lateral impact loading, from shear- to flexural-dominated, with a reduction of the impact damage. This strategy has a beneficial effect given sufficient bending capacity of the plain RC column.